Regional integration and public policy. Evaluation of the European experience and possible implications for Latin American integration - Tugores, Juan (CEPAL [Santiago]CL, 2008)
Reviews the analysis made of the impact of the trade opening processes on the various components of an economy. Describes the European experience and delves into the scope of the commitments spelled out in 'cohesion policies' as well as the myriad polemics surrounding their effectiveness. Discusses how some of the lessons from the European case can be extrapolated to the integration processes of Latin America and Caribbean countries.